A simplified equation for the collapse pressure of sandwich pipes with different core materials. (15th June 2022) - Fu, Guangming; Li, Mingliang; Yang, Jiankun; Li, Shuxin; Sun, Baojiang; Estefen, Segen F.
Abstract: Sandwich pipe with high-pressure resistance and the adequate insulation performance is a potential deepwater offshore oil and gas development solution. This paper establishes a two-dimensional finite element numerical model for sandwich pipe collapse prediction under external pressure using the finite element software ABAQUS. The developed numerical model is validated successfully using experiments in the literature. Parametric modeling is implemented with the help of the scripting language Python. A total of 3125 FEM models are established to analyze the influence of the sandwich pipe's geometric parameters, material properties, and interlayer adhesion properties on the collapse strength. The results show that the sandwich pipe's geometric parameters and core layer materials significantly influence the collapse strength. In contrast, the change of steel pipe steel grade has less influence. Moreover, the interlayer adhesion properties can significantly improve the collapse strength of the sandwich pipe. Finally, based on the numerical simulation results, a simplified equation for the collapse strength of the sandwich pipe is proposed for different core layer materials under frictionless interlayer conditions, which has an average error of 6.98% under the present assumptions. Highlights: The 2D finite element models are established and verified by full-scaled experiments. Parametric modeling of SPs is implemented and 3125 FE models are established to analyze the collapse behavior of SPs. A simplified equation for the collapse pressure of SPs with different core materials is established.